Microflora of the oral cavity in newborns immediate postpartum. - Edith Minaya-Flores (2020)
The oral microflora is a very varied ecosystem, however, before natural birth our oral cavity is completely sterile, but it is at the time of birth where the colonization of different microorganisms begins because when the fetus comes into contact through the birth canal, these microorganisms are able to adhere to the mucous membranes and begin such colonization in the newborn. Objectives The present research work is aimed at what may happen microbiologically in the first minutes of extrauterine life, i.e. the presence of microorganisms in the oral cavity of the newborn after immediate natural childbirth and as well as the relationship that exists between the microflora and natural childbirth. Materials and Methods For this study 25 newborn patients were considered for euthocic labor, from which 50 samples of their oral cavity were collected from the Goyeneche Hospital, Arequipa-2017. Results The collected samples were analyzed with Escherichia Coli and Staphilococcus Epidermidis in their buccal cavity. Conclusions There is a relationship between the presence of microorganisms and natural childbirth; therefore, the hypothesis is accepted: The greater the time of birth: of birth, of crowning and that passes from the rupture of membrane until the birth; there is a greater probability of presence of microorganisms in the buccal cavity of the newborns.